Clinical significance of the lymph node ratio in N1 breast cancer - Kim, Jaeho; Kim, Jin Hee; Kim, Ok Bae; Oh, Young Kee; Park, Seung Gyu (Radiation oncology journal, 2017)
The purpose of this study was to evaluate the prognostic value of the lymph node ratio (LNR), which was defined as the proportion of involved nodes of all dissected nodes, in pN1 breast cancer. We retrospectively analyzed the clinical data of patients with pN1 breast cancer (N = 144) treated at Keimyung University Dongsan Medical Center, Daegu, Korea between 2001 and 2010. The median age was 46 years (range, 27 to 66 years). The LNR was 0.01-0.15 (low LNR) in 130 patients and >0.15 (high LNR) in 14 patients. Sixty-five patients (45.1%) had T1 tumors, 74 (51.4%) had T2 tumors, and 5 (3.5%) had T3 tumors. Eighty-eight patients (61.1%) underwent total mastectomy and 56 (38.9%) underwent partial mastectomy. Fifty-nine patients (41.0%) underwent radiotherapy and 12 (8.3%) underwent regional radiotherapy. The median follow-up period was 65 months. The 5- and 10-year disease-free survival (DFS) rates were 92.7% and 82.4%, respectively. Univariate analyses revealed that high LNR (p = 0.004), total mastectomy (p = 0.006), no local radiotherapy (p = 0.036), and stage T2 or T3 (p = 0.010) were associated with worse DFS. In multivariable analysis, only high LNR (p = 0.015) was associated with worse DFS. High LNR is an independent prognostic factor in pN1 breast cancer and could be an indication for adjuvant radiotherapy in these patients.